CINEMATIC REFLECTION ON WILDLIFE: EXPLORING OF WILDLIFE NARRATIVES IN THE WEB SERIES “POACHER" - Mathur, Ashwarya; Pareek, Aditi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study explores the representation of wildlife and the ethical implications of poaching as illustrated in the “Poacher” series of eight episodes available on Amazon Prime. The portrayal of wildlife in cinema has evolved significantly, reflecting changing societal attitudes towards conservation and environmental stewardship. This research paper examines the web series "Poacher," exploring its narrative techniques, character portrayals, visual representation of wildlife conservation efforts. By analyzing episodes of "Poacher" and conducting thematic content analysis, this paper aims to understand how the series addresses wildlife-related issues and contributes to public awareness and discourse. Through this case study, broader insights into the intersection of cinema, wildlife conservation, and public perception are discussed. The findings reveal an exact portrayal of the socio-environmental dynamics of poaching and highlight the role of media in shaping conservation dialogue.